c.1 - "Aiyar, S.K." (Allahabad, 1983)
Of late the dacoity menace and broadday light robberies with free use of fire arms and explosives are raising their head posing law and order situation for the administrators of law and order. Therefore the restrictions on the free acquisition and use of firearms is certainly necessary in the interest of the general public. Many situations can be visualised when the uncontrolled use of firearms may be detrimental to the interests of the general public, violent revolutions may be encouraged, wild games may be exterminated, murder and arson might be resorted to and peaceful structure of society may be destroyed. At the same time possession of firearms in the hands of desirable persons may be a protection and safeguard against unruly elements and wild animals. They may also be required by peaceful citizens for entertainment and recrea tion, such as shooting exercises, wild games, etc. The State, therefore, has to intervene and put restriction on their user to protect the general public, with out at the same time destroying the fundamental right. In short the 'Arms' and 'Explosives' are very important subjects by themselves and should be given wide publicity as far as possible to educate all concerned and with this end in view the Author and Publishers have presented this book to the reading public and legal profession.
Keywords: Arms and Armor- India -Law and legislation